Milk casein and fatty acid fractions in early lactation are affected by nutritional regulation of body condition score at the beginning of the transition period in primiparous and multiparous cows under grazing conditions. Issue 5 (17th August 2012) - Artegoitia, V.; Meikle, A.; Olazabal, L.; Damián, J. P.; Adrien, M. L.; Mattiauda, D. A.; Bermudez, J.; Torre, A.; Carriquiry, M.
Summary The objective was to evaluate the effect of body condition score (BCS) at 30 days before calving (−30 days) induced by a differential nutritional management, parity and week of lactation (WOL) on milk yield and composition, and milk casein and fatty acid composition. Primiparous and multiparous Holstein cows with high BCS (PH, n = 13; MH, n = 9) and low BCS (PL, n = 9; ML = 8) under grazing conditions were sampled at WOL 2 and 8 (before and after peak of lactation). Milk yield was greater in multiparous than in primiparous cows and tended to decrease from WOL 2 to 8 only in ML cows. Milk protein, fat and casein yields were greater in multiparous than in primiparous cows and decreased from WOL 2 to 8. Milk casein concentration in milk protein was greater in MH cows than in ML, PH and PL cows at WOL 2. Milk κ‐casein was greater, and β‐casein was less in multiparous than in primiparous cows. As lactation progressed, proportion of casein fractions were not altered. Only κ‐casein fraction was affected by BCS at −30 days as PL showed a higher concentration than PH. The de novo (4:0–15:1) and mixed‐origin fatty acids (16:0–16:1) in milk fat increased, whereas preformed fatty acids (≥17:0) decreased from WOL 2 to 8. Saturated (SAT) fatty acids tended to be greater and monounsaturated fatty acids (MUFA) were less in multiparous than in primiparous cows. High‐BCS cows had greater concentrations of polyunsaturated (PUFA), conjugated linoleic acid (CLA) as well as n‐6 and n‐3 fatty acids in milk fat than low‐BCS cows. The results indicate that casein and fatty acid fractions in milk were affected by parity and may be modified by a differential nutritional management during the pre‐calving period (BCS at −30 days) in cows under grazing conditions.